1994
DOI: 10.1038/372773a0
|View full text |Cite
|
Sign up to set email alerts
|

Sunburn and p53 in the onset of skin cancer

Abstract: Squamous cell carcinoma of the skin (SCC) can progress by stages: sun-damaged epidermis, with individual disordered keratinocytes; actinic keratosis (AK), spontaneously regressing keratinized patches having aberrant cell differentiation and proliferation; carcinoma in situ; SCC and metastasis. To understand how sunlight acts as a carcinogen, we determined the stage at which sunlight mutates the p53 tumour-suppressor gene and identified a function for p53 in skin. The p53 mutations induced by ultraviolet radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
989
7
49

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,387 publications
(1,083 citation statements)
references
References 23 publications
38
989
7
49
Order By: Relevance
“…If p53 is mutated or inactivated in some manner, the apoptotic response is not activated and cell proliferation is allowed. Analysis of cells and tissues of p53-null mice has shown that functional p53 is necessary for DNA damage-induced apoptosis of cortical thymocytes (Clarke et al, 1993), myeloid progenitor cells (Lotem and Sachs, 1993), marrow preB cells (Strasser et al, 1994), quiescent peripheral B and T lymphocytes (Strasser et al, 1994), keratinocytes (Ziegler et al, 1994) and small intestine cells .…”
Section: Role Of P53 In Growth Arrestmentioning
confidence: 99%
“…If p53 is mutated or inactivated in some manner, the apoptotic response is not activated and cell proliferation is allowed. Analysis of cells and tissues of p53-null mice has shown that functional p53 is necessary for DNA damage-induced apoptosis of cortical thymocytes (Clarke et al, 1993), myeloid progenitor cells (Lotem and Sachs, 1993), marrow preB cells (Strasser et al, 1994), quiescent peripheral B and T lymphocytes (Strasser et al, 1994), keratinocytes (Ziegler et al, 1994) and small intestine cells .…”
Section: Role Of P53 In Growth Arrestmentioning
confidence: 99%
“…However, the p53 missense mutations harbored by HaCaT alleles are indeed UVB signature mutations (Pfeifer and Besaratinia, 2009, and references therein). Two apparently contradictory results blur our vision as to the role of p53 in skin cancer: mice deficient for TP53 develop tumors resembling SCC after UV irradiation (Ziegler et al, 1994;Li et al, 1998;Jiang et al, 1999), whereas Li-Fraumeni syndrome patients, who have a germline mutation in TP53, are not reported to be at increased risk for SCC (Malkin et al, 1990). These findings should be put in the perspective of the growing body of evidence showing that p53 missense mutants not only lose normal p53 functions, but are also often pro-active in tumor formation (reviewed by Donzelli et al, 2008;Brosh and Rotter, 2009).…”
Section: Activation Of Klf4 By Mutant P53mentioning
confidence: 99%
“…p53 is also an established cancer gene in CSCC 40, 41, 42 and HNSCC 43. Although p53 levels in cutaneous SCC are less characterized, somatic mutations of TP53 are frequently found in many typical tumors including CSCCs, which is then likely to compromise p53 function 44.…”
Section: Notch Signaling In Cutaneous Squamous Cell Carcinoma (Cscc)mentioning
confidence: 99%